Valoración económica de huertos agroecológicos en el cantón Loja - Jaramillo Figueroa, Ana Gabriela (2017)
Agro-ecological production offers benefits due to the use of environmentally friendly practices. However little is known about the additional economic benefits to farmers originated at the farm, which do not have a market value that defines them. The present study aims to determining the economic valuation of ten agroecological orchards of the parishes of El Valle and San Lucas of Loja canton, belonging to the RAL to figure it out the additional benefits of agroecology. For this, information about direct incpme by sale of products, and indirect benefits (avoided costs, savings and hedonic prices) was collected to calculate the total value that the orchards contribute to the family economy. As a result, agroecological orchards can generate an average of $ 71.770 annual income per hectare. It should be noted that this value consists of 29% of monetary income, 12% of monetary saving, 58% of avoided costs and 1% of surplus land. Revenues vary depending on the type of crop being short cycle varieties the most profitable. Owners who gave added value to production received higher incomes than those who did not.